Lectotypification of two Stegolepis names (Rapateaceae) - Rodrigues, Rodrigo Schütz (Phytotaxa, 2018)
Stegolepis Klotzsch ex Körnicke (1872: 480) is the largest genus of Rapateaceae and comprises 33 species endemic to the Guiana Shield in northern South America (Berry 2004). Most Stegolepis names have no problems concerning their typification. However, as part of ongoing floristic studies on the Rapateaceae of the Brazilian Amazonia and adjacent Guiana Shield areas (Rodrigues & Flores 2010, 2017; Rodrigues 2017), I found that two early names of Stegolepis are in need of lectotypification.